Job satisfaction among employees at the Iskandar Regional Development Authority (IRDA), Johor / Hasanah Ahmad - Ahmad, Hasanah (Faculty of Business and Management, 2010)
Job satisfaction among employees in an organization, especially for the authority body in Malaysia is becoming area of major concern as it has been highlighted for the most of that research that had been done. The job satisfaction will influence the effectiveness and efficiency of employees’ job. Literature validates that factors such poor working conditions, staff shortages, below competitive salaries, a lack of promotional opportunities are the some major factors that will create employee dissatisfaction within the sector (Ellickson & Logsdon, 2002: Herman, 2005: Ting 1997). The primary objective of this study is to ascertain level of job satisfaction amongst employees at the Iskandar Regional Development authority (IRDA). Then this study also to indicate whether there are significant relationship between job satisfaction with pay, promotion, supervisor, co-workers and work. The measurement of job satisfaction consist of five job facets which are pay, promotions, supervision, co-workers and the work itself For the purpose of this study a descriptive, simple random sampling design was used to measure job satisfaction. The sample group (N = 34) consist all department in IRDA. Results indicate that employees in IRDA are at medium level of job satisfaction. Therefore the job satisfaction in IRDA only has significant relationship with pay, promotion, supervisor and co-workers. Therefore IRDA should retraining management to come out with new method in improving the four facets of job satisfaction which are pay, promotion, co-workers and supervisor. Therefore, it is recommended that a proportionate stratified random sample be utilized for future research.